Formal Symbolization Within Spatial Imagination - I Made Bendi Yudha (Institut Seni Indonesia Denpasar, 2010)
The Balinese people are known to be religious. In their daily life activities on the implementation of the religious ritual called panca yadnya (five kinds of sacred rituals), always equipped with the means upakara or offerings are laden offerings with a variety of shapes and images in the form of symbols which are religious magical. The art of offerings is the art of symbols in which concrete and abstract could create artistic as well as symbols of supernatural characters; ten characters, five characters which are applicable and have different functions. And sometimes contradictory according to the needs and intended use. From these observations arose the interpretation of a meaning that, in meeting the needs of human life, basically has two major potential attractions to each other and complementary, i.e. doing structuring/restructuring or order which is oriented on the arrangement of a better life. The deviation/dissension and, even, destruction or chaos that tends to reject the establishment. This is when management is not based on the concept of balance and harmony, it will affect the social fabric of society and is prone to conflict and discord. Hence, the joints destabilize the integrity of nation and state. The concept of the balance contained in the upakara or offering means in comparison to the meaning of life phenomena that occur in society today seems to have been neglected and even abandoned. This can be proven where there has been deviation measures both the nature and the human life, among others, the exploitation of natural resources, discrimination in law and human rights, gender, and abuse of authority in the field of public administration, and will impact the spread of ecological crisis and moral degradation, as well as heighten the level of community poverty. Based on the understanding of the symbols mentioned above, these can be used as an interactive experience as well as a source of inspiration, a creator of images to stimulate natural trigger for the emergence of a sense that if copyright in the form of creative ideas about the values of life. The utterance of his philosophical concepts are abstracted into a work of art by combining with a representative form abstractive application through lines, colors and textures which are varied, and through impasto technique so that they reflect the authen- ticity of works of art (authenticity of the art work), aesthetic, artistic and reflection of personal value of novelty.